Morphosemantic fields in the building of the Croatian WordNet: the verbs of movement - Katunar, Daniela (Array, 2011)
The paper deals with a possibility of integration of morphosemantic relations into the structure of the Croatian WordNet. We argue that the theoretical framework of the morphosemantic field model can provide a far more extensive insight into the structure of the morphosemantic relations than the more formal approaches. The morphosemantic field model, relying on the tenets of cognitive linguistics, is able to account for those semantic relations that can hardly be explained by means of traditional morphological inquiries into the formation of meaning through derivation. On the basis of the analysis of the morphosematic field of movement the paper shows the full complexity of morphosemantic relations and makes them more explicit, thus allowing for their systematic future implementation into the Croatian WordNet.